Elisabeth Lambert Ortiz (contributing editor): The Encyclopaedia of Herbs, Spices, and Flavourings - Davidson, Alan E (Petits Propos Culinaires, 1992)
Elisabeth Lambert Ortiz (contributing editor): The Encyclopaedia of Herbs, Spices, and Flavourings: Dorling Kindersley, London, 1992: 290 pp, uncountable colour illustrations, one-page bibliography, well-presented index, large (A4) format, £19.99. (There is also a US edition, from Dorling Kindersley Inc, New York, priced at 34.95.)